2020
DOI: 10.3390/cells9010230
|View full text |Cite
|
Sign up to set email alerts
|

RhoA-GTPase Modulates Neurite Outgrowth by Regulating the Expression of Spastin and p60-Katanin

Abstract: RhoA-GTPase (RhoA) is widely regarded as a key molecular switch to inhibit neurite outgrowth by rigidifying the actin cytoskeleton. However, during neurite outgrowth, whether and how microtubule dynamics are regulated by RhoA remains to be elucidated. Herein, CT04 and Y27632 were used to inactivate RhoA and its downstream effector Rho-associated coiled coil-forming kinase (ROCK), while the RhoAQ63L lentiviral vector was utilized to overexpress the constitutively activated RhoA in dorsal root ganglion (DRG) neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The RhoA pathway is previously demonstrated associating with dendrite development and axonal extension (Tan et al, 2020). Also, our RNA-seq analysis indicated that the Rho GTPase binding activity could be influenced after RF-EMF exposure.…”
Section: Creb and Rhoa Are Involved In Epha5 Signaling Which Mediates The Effects Of Rf-emfsupporting
confidence: 57%
“…The RhoA pathway is previously demonstrated associating with dendrite development and axonal extension (Tan et al, 2020). Also, our RNA-seq analysis indicated that the Rho GTPase binding activity could be influenced after RF-EMF exposure.…”
Section: Creb and Rhoa Are Involved In Epha5 Signaling Which Mediates The Effects Of Rf-emfsupporting
confidence: 57%
“…It is unclear how DNA damage or OGG1 intracellular signaling might alter outgrowth. Signaling by RhoA in sensory neurons has been shown to negatively regulate neurite outgrowth [68]. Cisplatin could enhance RhoA activation via engagement of OGG1:8-oxydG signaling to induce neurite retraction, and thus inhibition of OGG1 could reverse the effects of cisplatin to decrease outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…ROCKs are important effectors of Rho in regulating the actin cytoskeleton and have been believed to extensively involve in the biological processes of cell migration, movement, apoptosis, gene transcription, and neural regeneration . It has been reported that the Rho/ROCK signaling pathway is related to the secretion of neurotransmitters in the myelin sheath, which subsequently changes the cytoskeleton structure and causes the collapse and contraction of growth cones, limiting the growth of neurites. Therefore, the initial outgrowth of neurite was very sensitive to the extracellular matrix (ECM) environment and further regulated the subsequent neurogenesis. The significantly downregulated expression of neurogenesis-related protein and RNA markers of all of the groups after adding the ROCK inhibitor (Y27632) confirmed the key role of actin cytoskeleton dynamics during the neurogenesis process in this study (in comparison of Figures and ). Although the exact mechanism underlying surface hydroxyl group features regulating the neurogenesis process still needs to be further explored, the absent expression of the GAP-43 protein to be detected in all three groups after 1 day of culture after adding Y27632 suggested that the regulation might be more influential at the early stage of neurogenesis (Figure A,C).…”
Section: Discussionmentioning
confidence: 99%